Author Correction: Electronic origin of hydrogen storage in MOF-covered palladium nanocubes investigated by synchrotron X-rays. Issue 1 (December 2018) - Chen, Yanna; Sakata, Osami; Nanba, Yusuke; Kumara, Loku; Yang, Anli; Song, Chulho; Koyama, Michihisa; Li, Guangqin; Kobayashi, Hirokazu; Kitagawa, Hiroshi
The previously published version of this Article contained an error in Fig. 1. In panel c, the thickness of the HKUST-1 layer (3 nm) was incorrectly labelled. This error has been corrected in both the PDF and HTML versions of the Article.